Osteoclasts: what do they do and how do they do it? - Teitelbaum, Steven L. (Henry Stewart Talks, 2012)
Osteoclast, Osteoporosis, Bone remodeling, Osteopetrosis, Mechanisms of osteoclast formation, Mechanisms of osteoclastic bone resorption, Osteoclast cytoskeleton